Template-assisted fabrication of nanostructured tin (β-Sn) arrays for bulk microelectronic packaging devices - Sharma, Ashutosh; Srivastava, Ashok K.; Jeon, Yongho; Ahn, Byungmin (Metals, 2018)
In this study, uniform and ordered nanostructured arrays of pure tin (Sn) were produced by the chemical pulse plating method in potentiostatic mode. Bottom metalized anodic aluminium oxide templates were used as the substrates for holding nanostructures during deposition. The plating bath consists of stannous sulfate (SnSO4), sulfuric acid (H2SO4), polyethylene glycol (PEG), and glutaraldehyde as a surfactant. The effect of potentiostatic potential ranging from −0.5 to −3.2 V vs. Ag/AgCl electrode was studied on the growth morphology of nanostructures that were formed. The characterization studies were accomplished by X-ray diffraction (XRD), field emission electron microscopy, and energy dispersive spectroscopy. It was found that several nanostructures were of different shapes and size when the potential was varied. Nanorods were prominent at the deposition potentials of −0.5 and −1.1 V, while a combination of nanostructures (nanorods, nanoplates, and nanoparticles) was predominant at −3.2 V. XRD results show that the nanostructures that were obtained consisted of tetragonal (Sn) structure with a crystallite size of about 20 nm. This process is economically viable and it can be scaled to produce various nanostructures through a careful control of deposition parameters.
Keywords: Bulk; Deposition; Nanorods; Nanostructure; Plating; Pores; Template